Optimization of the microencapsulation of lemon myrtle oil using response surface methodology - Huynh, T.; Caffin, N.; Dykes, Gary; Bhandari, B. (Taylor and Francis Inc, 2008)
Response surface methodology (RSM) was applied to study the effects of types of wall materials (modified starch + maltodextrin and whey protein concentrate + maltodextrin), feed concentration, oil concentration, and outlet air temperature on oil retention and surface oil content of the encapsulated powder. The results revealed that the oil retention was significantly (P < 0.05) affected by the constant term of types of wall materials and the linear term of feed concentration but seemed to be almost independent (P > 0.05) of experimental range of oil concentration and outlet air temperature. The types of wall materials, oil load, and outlet air temperature showed a significant (P < 0.05) influence on surface oil content. The types of wall materials (Hi-Cap and WPC) also influenced significantly the oil retention and surface oil content. Based on the limited range of experimental conditions used in this work, it was not possible to choose the wall materials that can give both high oil retention and low surface oil content. Disregarding the effect of wall material, an optimum response was obtained at 40% of feed concentration (w/w), 18% of oil concentration, and 65°C of outlet air temperature.